EVALUASI PERAN STOREKEEPER DALAM PENGELOLAAN PERSEDIAAN BARANG DI HOTEL HARRIS GUBENG SURABAYA - Habibullah, Ulil; Yuliati, Anik (Jurnal Riset Ilmu Akuntansi, 2026)
The Storekeeper plays a crucial role in ensuring the smooth operation of hotel activities, particularly in managing the inventory of goods required by various departments. This study aims to describe the Storekeeper’s role and identify the challenges faced in inventory management at Harris Hotel Gubeng Surabaya. The research employs a descriptive qualitative approach, with data collected through direct observation, interviews, and documentation during an internship. Findings indicate that although the inventory system utilizes the VHP application and is supported by manual bincards, discrepancies between system records and physical stock still occur due to inconsistent recording practices. Additionally, slow-moving items were found accumulating in the warehouse without proper evaluation or usage plans. These findings highlight the need for improved accuracy in inventory recording and periodic evaluation of inventory items to enhance warehouse efficiency in hotel operations.